Encounter earth interactive geoscience explorations - Kluge, Steven (Upper Saddle River, NJ Pearson education, 2009)
"Ideal for professors who want to integrate Google Earth7F!" in their classrooms, Pearson's new 'Encounter Earth' supplement gives students a new, well-organized way to visualize key topics in their introductory geoscience courses. This guide saves instructors assignment preparation time, and helps students find Google Earth7F!" locations for assignments created." -- Site Web de l'?editeur
1. Using Google Earth7F!" -- Exploration 2. Interpreting Topographic Maps -- Exploration 3. Running Water: Stream Dynamics -- Exploration 4. Deposition: Angle of Repose -- Exploration 5. Mass Wasting: Landslides -- Exploration 6. Groundwater and Karst -- Exploration 7. Alpine Glaciation: Active Ice -- Exploration 8. Alpine Glaciation: After the Ice -- Exploration 9. Continental Glaciation: After the Ice --Exploration 10. Shorelines -- Exploration 11. Plate Tectonics: Divergent and Transform Boundaries -- Exploration 12. Plate Tectonics: Convergent Boundaries -- Exploration 13. Volcanism: Global Distribution of Volcanoes -- Exploration 14. Volcanism: Lava Flows -- Exploration 15. Volcanism: Calderas -- Exploration 16. Structural Geology: The Boulder Flatirons -- Exploration 17. Geologic History: Dinosaur Ridge -- Exploration 18. Geologic History: Red Rocks -- Exploration 19. Natural Hazards -- Exploration 20. Impact Structures.
Keywords: Google Earth (Logiciel) -- Probl?emes et exercices; Google Earth -- Problems, exercises, etc; Sciences de la terre -- Probl?emes et exercices; G?eologie -- Probl?emes et exercices; Geographic information systems -- Problems, exercises, etc; Earth sciences -- Problems, exercises, etc; Geology -- Problems, exercises, etc